2012
DOI: 10.1016/s1474-4422(12)70241-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systolic blood pressure on white-matter integrity in young adults in the Framingham Heart Study: a cross-sectional study

Abstract: Summary Background Previous studies have identified effects of age and vascular risk factors on brain injury in elderly individuals. We aimed to establish whether the effects of high blood pressure in the brain are evident as early as the fifth decade of life. Methods In an investigation of the third generation of the Framingham Heart Study, we approached all participants in 2009 to ask whether they would be willing to undergo MRI. Consenting patients underwent clinical assessment and cerebral MRI that incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
269
5
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(297 citation statements)
references
References 53 publications
17
269
5
6
Order By: Relevance
“…It is possible that vascular dysautoregulation related to vascular factors such as smoking, hypertension, and diabetes can cause transient reductions in blood flow to white matter watershed areas of vascular supply, which in turn results in transient hyporemia, hypoxemia, and subtle myelin injury. 22,30,31 We found an interaction between APOE e4 and vascular risk factors that affected white matter microstructure. ApoE has a major role in transporting lipid components that contribute to building up the myelin sheath.…”
mentioning
confidence: 73%
“…It is possible that vascular dysautoregulation related to vascular factors such as smoking, hypertension, and diabetes can cause transient reductions in blood flow to white matter watershed areas of vascular supply, which in turn results in transient hyporemia, hypoxemia, and subtle myelin injury. 22,30,31 We found an interaction between APOE e4 and vascular risk factors that affected white matter microstructure. ApoE has a major role in transporting lipid components that contribute to building up the myelin sheath.…”
mentioning
confidence: 73%
“…Distribution of moderate nAChR density in temporal parietal cortices and low levels in white matter tracts could make IFOF more vulnerable to aberrant AChR function. Furthermore, the IFOF is in a brain region that undergoes continued organization in early adulthood38 and is particularly vulnerable to vascular risk factors 39…”
Section: Discussionmentioning
confidence: 99%
“…A recent epidemiologic study in the cohort of participants in the third generation of the Framingham Study showed that hypertension begins to cause white-matter damage in middle age, supporting aggressive treatment of hypertension in mid-life. 142 This has lead to a reassessment of the normal range of blood pressure at various ages since it may be beneficial to aggressively lower blood pressure in the younger hypertensive patients, while avoiding excessive blood pressure lowering in the very old, although the age boundaries are still to be determined. 143 While it remains a challenge to separate inflammation from multiple lacunar strokes as the primary mechanism of injury to the white matter, the interaction between ischemia and Inflammation is an emerging concept that may be relevant in those individuals with progressive decline rather than discreet strokes.…”
Section: An Approach To Targeted Treatment Trialsmentioning
confidence: 99%